2018
DOI: 10.1002/asi.24129
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic motivation, task reflexivity, and knowledge contribution behavior on team wikis: A cross‐level moderation model

Abstract: A cross-level model based on the information processing perspective and trait activation theory was developed and tested in order to investigate the effects of individual-level epistemic motivation and team-level task reflexivity on three different individual contribution behaviors (i.e., adding, deleting, and revising) in the process of knowledge creation on team wikis. Using the Hierarchical Linear Modeling software package and the 2-wave data from 166 individuals in 51 wiki-based teams, we found cross-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 55 publications
(137 reference statements)
2
19
0
Order By: Relevance
“…To save time, physicians can summarize the common questions they encounter and publish the answers on the online health platform. They can then use this knowledge to improve their professional knowledge capability, which increases the possibility of publishing relevant articles on the online health platform ( Zhang et al, 2019a ; Meng et al, 2021 ). In addition, a higher number of patient consultations show that physicians are interacting with patients on the platform more; that is, physicians are more involved in the platform.…”
Section: Theory Background and Hypothesesmentioning
confidence: 99%
“…To save time, physicians can summarize the common questions they encounter and publish the answers on the online health platform. They can then use this knowledge to improve their professional knowledge capability, which increases the possibility of publishing relevant articles on the online health platform ( Zhang et al, 2019a ; Meng et al, 2021 ). In addition, a higher number of patient consultations show that physicians are interacting with patients on the platform more; that is, physicians are more involved in the platform.…”
Section: Theory Background and Hypothesesmentioning
confidence: 99%
“…Co-editing of online encyclopedia has been extensively explored. Earlier research focuses on the individual collaborative behavior, such as the taxonomy for categorizing contributors' actions (Pfeil et al, 2006), motivations of participating in co-editing (Arazy and Gellatly, 2013), the effects of personal traits (Zhang et al, 2018), etc. Some research has explored co-editing from a technical perspective, including the implementation of the co-editing system (Li et al, 2004), and the interaction interface (He and Han, 2006).…”
Section: Co-editing Of Online Encyclopediamentioning
confidence: 99%
“…technology and management) about co-editing, such as the function and interaction interface of wiki system (Li et al, 2004;He and Han, 2006), the organization of contributors (Miller, 2005;Nov, 2007), editing coordination (Kittur and Kraut, 2008), conflict management and so on. A few studies focus on co-editing activities, such as encyclopedia contributors' behaviors and co-editing patterns (Kittur and Kraut, 2008;Kimmerle et al, 2010;Zhang et al, 2018). However, the scholarly literature has offered little guidance on exploring co-editing mechanism from the perspective of content creation.…”
Section: Introductionmentioning
confidence: 99%
“…HRM scholars, on the other hand, focus on HRM practices that intend to develop KM skills and behaviors of teams to promote the acquisition, exploration, and exploitation of knowledge (Chuang et al, 2016; Shahzad et al, 2022). Although both streams highlight important determinants and mechanisms of team performance, how KM technologies and HRM practices can be integrated to promote knowledge development within teams or, according to IS scholars, how such teams systematically deploy KM technologies to develop and update unique knowledge, to effectively perform in a dynamic knowledge‐intensive environment (e.g., see Jarrahi & Sawyer, 2015; Wang et al, 2018; Zhang et al, 2019) is still undertheorized in a KIT context. It is an important gap this study intends to address.…”
Section: Introductionmentioning
confidence: 99%
“…Our study's motivation to consider knowledge sharing and reflexivity is based on the conceptual and empirical evidence that KIT perform in a complex and dynamic knowledge‐intensive environment where the key to success is to expand and continuously upgrade the team's knowledge resources and capabilities (Massey et al, 2002; Monks et al, 2016; Schippers et al, 2013). Knowledge sharing and reflexivity are critical processes that facilitate the team's adaptability processes by promoting information exchange and collective learning (Cao et al, 2021; Schippers et al, 2015; Zhang & Guo, 2019; Zhang et al, 2019), leading to superior team performance (Wang et al, 2021). Although Shahzad et al (2022) have identified knowledge exploration and exploitation as critical mechanism of HRM practices to influence team performance, their conceptualization offers a relatively static view of teams' external knowledge acquisition and utilization and thus does not explain as how teams internally adapt and adjust during the performance process to match continuously changing environment.…”
Section: Introductionmentioning
confidence: 99%